The Use of Spinning Media as an Information Service to Improve Student Career Planning - Reza Rudianti Sari; Kadek Ari Dwiarwati (Bisma The Journal of Counseling, 2023)
Career planning is an effort someone makes to determine the career path to be achieved after completing the educational process. Only the reality on the ground shows that students' career planning abilities are still relatively low. This is evidenced by the many students still confused about where to go after high school education. This research aims to develop and test a spinning tool as an information service to improve student career planning. This research belongs to the type of development research, which was developed using the Brog and Gall model through the stages of potential and problem analysis, data collection, media planning, design validation, design reviews, media tests, and product versions. The subjects involved in this study were two counselors and 35 ninth-grade high school students. Data were collected using the questionnaire method, with research instruments like product validity sheets and career planning ability questionnaires. The data obtained were then analyzed using quantitative descriptive analysis techniques. The results show that the value of t count ≥ t table is 31.57 > 1.691, which means that Ho is rejected and Ha is accepted. Based on these results, it can be concluded that spinning media as an information service is effectively used in the guidance process because it can improve student career planning.